Analisis SWOT Dalam Menentukan Strategi Pemasaran Pada Fashion Brand - Muhamad Bayu Pramesta; Agus Rahayu; Puspo Dewi Dirgantari (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
The fashion business is a promising business because fashion ranks at the top of sales in the current era. Along with the development of technology, producers are increasing in creating product innovations they make. The tight competition in fashion requires manufacturers to take advantage of existing opportunities. This study aims to determine the right and competitive strategy by first identifying, through internal business factors and external environmental factors that influence the business. This is done using the SWOT Analysis method (Strength, Weakness, Opportunity, Threat). SWOT analysis is an analysis used to identify opportunities and threats in the business environment as well as evaluate the strengths and weaknesses of the internal business. The results of the research show that the strategy that can be applied is product development.